Exploring the Ophthalmic Features of Cornelia de Lange Syndrome: A Case Report - Radhika Paranjpe; Shikha Rai; Tushar Agrawal; Gufran Ali Kamdar (Journal of Clinical and Diagnostic Research)
Cornelia de Lange Syndrome (CdLS) is a rare genetic disorder that affects growth, development and various body systems, with symptoms ranging from mild to severe. The condition is marked by distinctive facial features such as arched eyebrows, long eyelashes, a small nose and a thin upper lip. Growth delays are noticeable both before and after birth, leading to short stature. Affected individuals often have limb abnormalities, including missing or underdeveloped fingers and toes, as well as cognitive impairments that can vary from mild to severe. CdLS is caused by mutations in genes crucial for early development, particularly those involved in forming facial, limb and brain structures. The most common mutations occur in the NIPBL, SMC1A and SMC3 genes, although other genetic factors may also contribute. These mutations disrupt normal cellular functions, resulting in the physical and developmental challenges characteristic of the disorder. Effective management of CdLS requires a collaborative approach involving a team of medical professionals, therapists and educators who work together to address the diverse needs of affected individuals. This may include Physical Therapy (PT) for limb abnormalities, speech therapy and Occupational Therapy (OT) to support cognitive and developmental progress, as well as regular monitoring of growth and health. A seven-year-old child presented with involuntary eye movements (horizontal nystagmus) in both eyes since early childhood, along with global developmental delay, reduced psychomotor skills and intellectual disability. Clinical findings included a unibrow, hirsutism, long eyelashes and visual acuity of 6/60 in both eyes, improving to 6/36 with correction.